Upholding the Honour of the Crown - McMorrow, Thomas (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2018)
In this paper, I aim to advance understanding of the constitutional principle of the honour of the Crown, by evaluating legal and political dimensions of the concept. I seek to demonstrate how the honour of the Crown may obscure but also illuminate legal issues and political challenges that meaningful pursuit of reconciliation involves. I argue that once one starts to ask “Who is to uphold the honour of the Crown?” one observes opaque royal symbolism obscuring, but also framing, contested questions of governance shot through with collective coordination problems. I argue that appreciating the normative potential of the “honour of the Crown” means acknowledging that the concept figures as but one of many communicative forms that may serve to foster a more just arrangement for and among peoples.